Neonatal gastric perforation: a report of two cases and a systematic review. Issue 17 (April 2018) - Chen, Tsung-Yen; Liu, Hsien-Kuan; Yang, Ming-Chun; Yang, Yung-Ning; Ko, Po-Jui; Su, Yu-Tsun; Huang, Ru-Yi; Tsai, Ching-Chung
Abstract: Rationale: Neonatal gastric perforation is a rare and life-threatening disorder in neonates and is associated with high morbidity and mortality. However, the exact mechanisms of neonatal gastric perforation remain unknown. Patient concerns: In this study, we reported 2 cases of neonatal gastric perforation and conducted a systematic review to analyze the prognostic factors for mortality. Diagnoses: Two neonates received a diagnosis of gastric perforation based on clinical presentation and imaging studies. The 2 patients underwent emergent surgery, which yielded favorable outcomes. Interventions: We reviewed 168 cases from the literature as well as our 2 cases to analyze whether mortality in neonatal gastric perforation is associated with sex, gestational age, operation type, perforation location, or timing of perforation. Outcomes: The results revealed that mortality was significantly higher in preterm neonates (n = 80, P < .01) and the mortality group had a lower birth weight (n = 73, P < .05). The timing of perforation in the preterm subgroup was significantly earlier than that in the full-term subgroup (n = 90, P < .05). The outcomes about mortality of gastric perforation were significantly associated with preterm neonates (adjusted odds ratio: 4.21, 95% confidence interval: 1.28–13.88, P < .05). Lessons: This study shows the prognostic factor of gastric perforation was significantly associated with preterm neonates. Furthermore, low-birth-weight full-term neonates had a relatively higher mortality rate than the normal-birth-weight full-term neonates. In addition, preterm neonates have an earlier timing of perforation.